Советская ПВО в годы войны - Широкорад Александр Борисович (1941-1945. Великая и неизвестная война, 2021)
Экземпляры: РБ (20210203☮) / Инвентарный номер: 60635 / Цена: 200.00 / Авт.знак: Ш 64 / ГРНТИ: 03 / ББК: 63.3(2)622